Life Cycle Assessment of Slaughtered Pork Production: A Case Study in Thailand: 10.32526/ennrj/22/20240074 - Joyroy, Monthita; Sriphirom, Patikorn; Buawech, Direkrit; Phrommarat, Bhanupong (Environment and Natural Resources Journal, 2024)
Pork is a staple food in many cultures worldwide and plays a significant role in global food systems. However, the production of pork is associated with various environmental issues throughout its life cycle. This study employed a life cycle assessment (LCA) to evaluate the environmental impact of slaughtered pork production in Thailand. The system boundaries encompassed pig breeding, pig farming, and slaughtering. The primary focus was on identifying significant contributors to environmental burdens throughout the pork production chain. Three scenarios for pig feed compositions were assessed. The results indicated that pork production generated a total impact of 5.07 kgCO2-eq on global warming, 1.16E-03 kgP-eq on freshwater eutrophication, 4.69 m2a-eq on land use, and 4.97 m3 on water consumption. Pig feed production, particularly maize cultivation, emerged as a hotspot within the life cycle, contributing the highest impact across all categories. According to scenario analysis, the substitution of rice by-products and sorghum in pig feed tended to reduce the magnitude of the impact. Opportunities were suggested to improve the environmental performance of pork production, especially through feed strategies such as substituting high-impact ingredients with more sustainable alternatives and utilizing waste from pig farming and slaughtering.